Analysis of Threat Risk and Vulnerability in Network Security Along with Countermeasures to Overcome the Damages in an Enterprise Network - Khan, Maroof; Sajjad, Gulab Jan (Journal for Research in Applied Sciences and Biotechnology, 2023)
The research is conducted based on analysis of threat, risk and vulnerability in an enterprise network along with countermeasures to overcome the security incidents in an enterprise network. It is clear that most of the businesses are running using internet to store and share data between employees and customers, because data are precious and an asset for an organization. So, there is a high chance of losing data due to threat, risk and vulnerability in an enterprise network. However, there is a need of awareness and understanding between threat, risk and vulnerability including countermeasures to protect data in rest and data in motion in a network. As well as information security aim to protect organizational data from unauthorized access, manipulation and destruction.